1985
DOI: 10.1136/pgmj.61.713.201
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular disease in dementia: the importance of atrial fibrillation

Abstract: Summary The relationship between cardiovascular disease and cerebral infarction was analysed in a prospectively assessed post mortem series of 48 demented patients. Hypertension was rare in this group of patients whose mean age was 82.7 y. Atrial fibrillation was the most important underlying cardiac abnormality. It is suggested that atrial fibrillation is more important than hypertension in the aetiology of cerebral infarction in the very aged and that this may be relevant to the pathogenesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The 3 questions are: Evidence supporting the association between AF and cognitive impairment in patients with stroke comes from both pathological and clinical studies. In 1985, Ratcliff et al 13 provided postmortem proof of the relationship between cardiovascular disease and cerebral infarction in a consecutive series of 48 demented patients (mean age, 82.7 years). Among underlying cardiac abnormalities, AF was strongly associated with cerebral infarcts and, consequently, relevant to the pathogenesis of dementia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The 3 questions are: Evidence supporting the association between AF and cognitive impairment in patients with stroke comes from both pathological and clinical studies. In 1985, Ratcliff et al 13 provided postmortem proof of the relationship between cardiovascular disease and cerebral infarction in a consecutive series of 48 demented patients (mean age, 82.7 years). Among underlying cardiac abnormalities, AF was strongly associated with cerebral infarcts and, consequently, relevant to the pathogenesis of dementia.…”
mentioning
confidence: 99%
“…Among underlying cardiac abnormalities, AF was strongly associated with cerebral infarcts and, consequently, relevant to the pathogenesis of dementia. 13 More recently, Dublin et al 14 reported postmortem data from the Adult Changes in Thought (ACT) study, a population-based prospective cohort study on dementia risk factors. Among the 328 individuals (mean age, 87.6 years), the presence of AF (41% of patients) significantly increased the risk of having a cerebral infarct.…”
mentioning
confidence: 99%
“…16 - 19 Silent infarcts detected by computed tomography (CT) have been found in 35-37% of nonrheumatic AF patients with no history of stroke. 16 - 17 In a preliminary report including patients with rheumatic and nonrheumatic AF but without previous stroke, CT evidence of previous stroke was 2.9-4.5 times as frequent as in non-AF patients.…”
mentioning
confidence: 99%
“…While these CT-defined infarcts are labeled asymptomatic or "silent," it is likely that they take a subtle, but cumulative, toll on cognition in elderly people. 19 Considering the combined risk of clinical and subclinical stroke, AF becomes a substantial threat to the brain.…”
mentioning
confidence: 99%
“…(Aliot, 2009) The presence of AF increases the risk for stroke, about 20% of all embolic strokes are associated with it. (Ratcliffe & Wilcock, 1985) There is increasing evidence that AF is associated with an increased risk of asymptomatic or silent cerebral infarction and as a result may confer an increased risk of progressive cognitive impairment. Most cases of AF are now of non-rheumatic or non-valvular (NVAF) aetiology.…”
Section: Af Stroke and Dementiamentioning
confidence: 99%